ANALISIS NILAI-NILAI MORAL DALAM NOVEL AZIMAH DERITA GADIS ALEPPO KARYA ARUM FAIZA - Milda Hastuti; Martono Martono; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research is entitled Moral Value Analysis in the Azimah The Suffering Of Aleppo Girl  novel by Arum Faiza. the background of this research was because study of literature especially Azimah the Suffering Of Aleppo Girl  novel by Arum Faiza never been studied, efforts to know moral values in life contained in the novel. The purpose of this study was to describe moral values seen from individual relationships with God, society and individuals in the Azimah the Suffering Of Aleppo Girl  novel by Arum Faiza and plans for implementing learning in schools. his research uses a descriptive method, in the form of qualitative, with a sociological approach to literature. The research data sources were the AzimahThe Suffering Of Aleppo Girl  novel by Arum Faiza, the data in the form of quotations identified have an indication of moral value. The data collection techniques with documentary study techniques. The data collection tool is the researcher himself as a key instrument. Technical data analysis used  content analysis methods or content analysis methods. Keywords:       analysis, moral values, novel